2015
DOI: 10.1038/nrurol.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of hypospadias: relevance of animal models

Abstract: | Hypospadias is a congenital abnormality of the penile urethra with an incidence of approximately 1:200-1:300 male births, which has doubled over the past three decades. The aetiology of the overwhelming majority of hypospadias remains unknown but appears to be a combination of genetic susceptibility and prenatal exposure to endocrine disruptors. Reliable animal models of hypospadias are required for better understanding of the mechanisms of normal penile urethral formation and hence hypospadias. Mice and/ or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(117 citation statements)
references
References 76 publications
3
105
0
9
Order By: Relevance
“…Mice are emerging as a powerful system for modeling human genitourinary defects, although there are notable differences in tissue morphogenesis and in signaling interactions that remain to be understood (47). For example, prenatal exposure to estrogen can feminize male external genitalia in humans (16,48,49) but has little effect in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice are emerging as a powerful system for modeling human genitourinary defects, although there are notable differences in tissue morphogenesis and in signaling interactions that remain to be understood (47). For example, prenatal exposure to estrogen can feminize male external genitalia in humans (16,48,49) but has little effect in mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prenatal exposure to estrogen can feminize male external genitalia in humans (16,48,49) but has little effect in mice. Such differences likely reflect differences in gestational time because humans have a relatively long period of prenatal development compared with mice and, therefore, the neonatal phase of genital development in mice is comparable with prenatal development in humans (47,50). Although the penis and clitoris are well-differentiated in human neonates (51), penile and clitoral differentiation in the mouse occurs mainly during the postnatal period (52).…”
Section: Discussionmentioning
confidence: 99%
“…The rat model shares common features of human hypospadias, such as disruption of the urethral meatus, prevalence of distal penile deformities, and failure of epithelial fusion (Cunha et al 2015). Some regulators of autophagy, such as mammalian target of rapamycin ( mTOR ) , can inhibit autophagy via the phosphoinositide 3-kinase (PI3K) / protein kinase B ( Akt ) signaling pathway ( Lum et al 2005 ) ; whereas Beclin 1 can upregulate autophagy ( He and Klionsky 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the reported CPA incidents have increased significantly, raising the speculation that in utero exposure to endocrine disrupting chemicals (EDCs) may be responsible for this increase. Published studies using either the mouse or rat model showed that developmental exposures to antiandrogen or estrogenic compounds can lead to a range of penile anomalies similar to human CPAs (2) Mammalian external genitalia development begins with the outgrowth of a genital tubercle (GT), which is the anlage of penis in males and clitoris in females. In mice, the GT develops as a pair of genital swellings around the cloaca and slightly caudal to the hindlimbs on embryonic day (E) 10.5 (Fig.…”
mentioning
confidence: 99%
“…Because of the long gestation period for humans (40 wk), in utero exposure to EDCs can span the whole length of human pregnancy, including both hormone-sensitive and -insensitive periods. The sensitive period to androgen disruption in mice corresponds to the first trimester of human pregnancy, whereas the estrogen-sensitive period corresponds to mostly the second trimester (2,9). Thus, if the EDC exposure window can be more precisely defined and separated into hormone-sensitive and -insensitive periods, epidemiological studies may be able to increase their predicative power as to whether in utero exposure to certain chemicals is associated with genital defects later in the adult.…”
mentioning
confidence: 99%